1990
DOI: 10.1007/bf00163552
|View full text |Cite
|
Sign up to set email alerts
|

HLA and uveitis

Abstract: The association between HLA-A29 and birdshot chorioretinopathy is the strongest of all associations between HLA and disease. Determination of HLA-A29 is even of diagnostic significance. The association between HLA-B27 and acute anterior uveitis (AAU) is much weaker, but B27 positive AAU may be considered as a distinct clinical entity. B27 positive patients with AAU should be referred to a rheumatologist, because half of these patients have ankylosing spondylitis or Reiter's syndrome. The determination of HLA-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…(Careless & Inman 1995) Such phenomenon was noted, for example, in K. pneumoniae. (Feltkamp 1990;Geczy & Yap 1979) It may be a cause of the cross-reaction (involving T lymphocytes) which, in response to bacterial antigens, may stimulate the production of antibodies that cross-react with HLA-B27 antigen of the host. Theoretically, this process could also promote the long-term survival of pathogens in host tissues because of cross-tolerance between the bacterial antigens and the host's HLA system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Careless & Inman 1995) Such phenomenon was noted, for example, in K. pneumoniae. (Feltkamp 1990;Geczy & Yap 1979) It may be a cause of the cross-reaction (involving T lymphocytes) which, in response to bacterial antigens, may stimulate the production of antibodies that cross-react with HLA-B27 antigen of the host. Theoretically, this process could also promote the long-term survival of pathogens in host tissues because of cross-tolerance between the bacterial antigens and the host's HLA system.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, this process could also promote the long-term survival of pathogens in host tissues because of cross-tolerance between the bacterial antigens and the host's HLA system. (Feltkamp 1990) According to another hypothesis, HLA-B27 acts like an alternative receptor which specifically reacts with some bacterial antigens and in this way modulates the response to infection. (Careless & Inman 1995) Analysing our data, we found a tendency towards slightly greater levels of anti-LPS antibodies in HLA-B27-positive patients than in HLA-B27-negative ones, but the observed differences were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of AMA isotype distribution showed that AMA are mainly in the IgG3 and IgM fractions [12][13][14]. These studies used four anti-human IgG subclass-specific MoAbs.…”
Section: Introductionmentioning
confidence: 99%
“…4 The probability of diagnosis of BSRC rises from 70 to 97% in HLA A-29 positive patients and decreases to 7.0% to 8.5% in HLA A29 negative patients. 5 Both HLA A29.1 and HLA A29.2 are associated with this ocular inflammatory disease. However, the presence of HLA-A29 does not imply that the patient will definitely develop BSRC.…”
mentioning
confidence: 98%